An analysis of permissible food and beverages according to halal and kashrut from Islamic perspective - Hariati Abubakar (International Institute of Islamic Thought and Civilization (ISTAC), International Islamic University Malaysia, 2020)
Some Muslims assume that kosher certified foods are permissible to be consumed based on the assumption that Jews do not consume swine and its by-products. The Qur'an also states in Surah al-Ma'idah verse 5 that, the food of those who received the scriptures (ahl al-Kitab) is permissible for consumption. Kashrut (Jewish dietary laws) shares some identical food principles with Islamic food laws especially on the issue of animal slaughtering and the prohibition of swine. These similarities lead to the assumption that kosher certified foods are halal for Muslims and thus those products can be considered as substitutes to halal products especially if the halal certified products are not available in the market. The objectives of this research are: to determine the factors that cause the lack of awareness among the Muslim consumers on kosher certified products, to analyze the similarities and differences between halal and kosher food principles particularly on halal and kosher food supply chains, to scrutinize the opinions of the Muslims scholars (intellectuals) on the issue of consumption of kosher food products from an Islamic perspective and lastly to propose guidelines for Muslim consumers regarding consumption of kosher certified products. The current study is qualitative in nature. The data used in this study was collected from library research and field researches (interviews). Then the data was analyzed based on content, comparative, inductive and deductive analysis. The research findings of this study show that the level of awareness among Muslim consumers on kosher certified products is low due to lack of knowledge and information on Jewish basic food principles (kashrut). There are some similarities and fundamental differences between kashrut and halal. Therefore, both are not identical or interchangeable. There is a misconception held by Muslim consumers that the consumption of kosher certified products is permissible since kashrut (Jewish Dietary Laws) prohibit swine in their products as applied in Islam. However, alcohol is permissible in kashrut (Jewish dietary Laws) provided that it is processed and produced by Jews. Alcohol is common ingredient (additive) in kosher food products. It may be added in plant and fish-based products which render kosher certified products unacceptable for consumption in Islam. Therefore, kosher certified products are not necessarily halal and cannot be considered as substitutes for halal certified products. On the issue of animals slaughtered by Jewish people, Muslim scholars are not unanimous regarding their permissibility.